Need Help?

Subscribe to Differential Equation

Subscribe
  • Notes
  • Comments & Questions

$$2 y^{\prime \prime}-\frac{1}{x-1} y^{\prime}+\frac{1}{(x-1)^{2}} y=0$$

$$(x-1) p(x)=(x-1)\left(\frac{-1}{x - 1}\right)=-1$$

$$(x-1)^{2} q(x)=(x-1)^{2}\left(\frac{1}{(x-1)^{2}}\right)=1$$

$$\rightarrow$$ Regular singular point

\$$x_{0}=1$$

$$y=\sum_{n=0}^{\infty} c_{n}(x-1)^{n+r} $$

$$y^{\prime}=\sum_{n=0}^{\infty}(n+r)cn(x-1)^{n+r-1}$$

$$y^{\prime \prime}=\sum_{n=0}^{\infty}(n+r-1)(n+r)cn(x-1)^{n+r-2} $$

$$\rightarrow$$ Substitution in D.E

$$2 \sum_{n=0}^{\infty}(n+r-1)(n+r) c n(x-1)^{n+1-2}-\frac{1}{x-1} \sum_{n=0}^{\infty}(n+r)cn(x-1)^{n+r-1}+\frac{1}{(x-1)^{2}} \sum_{n=0}^{\infty} c_{n}(x-1)^{n+r}=0$$

$$2 \sum_{n=0}^{\infty}(n+r-1)(n+1)c n(x-1)^{n+r-2}-\sum_{n=0}^{\infty}(n+r) c n(x-1)^{n+r-2}+\sum_{n=0}^{\infty} c n(x-1)^{n+r-2}=0$$

$$\sum_{n=0}^{\infty}\left[2(n+r)(n+r-1)cn-(n+r) c n+c n](x-1)^{n+r-2}=0 \rightarrow (1)\right.$$

When $$n=0 \quad \longrightarrow[2 r(r-1)-r+1]=0 \quad \rightarrow$$ Indical Equation

$$2 r^{2}-3 r+1=0 \rightarrow r_{1}=1 \quad r_{2}=0.5$$

From $$(1) : cn[2(n+r)(n+r-1)-(n+r)+1]=0 \longrightarrow(1)$$

$$y=\sum_{n=0}^{\infty} c n(x-1)^{n+r} $$

$$y_{1}=c_{0}(x-1)$$

$$y_{2}=c_0(x-1)^{0.5} $$

$$y=c_{1}(x-1)+c_{2}(x-1)^{0.5} $$

No comments yet

Join the conversation

Join Notatee Today!